2020
DOI: 10.1111/echo.14613
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial longitudinal strain, fitness, and heart failure risk factors in young adults

Abstract: Aims To investigate the relationship between fitness, heart failure (HF) risk factors (age, blood pressure, and obesity), and global/regional myocardial longitudinal strain in young adults undergoing stress testing. Methods Individuals 25–55 years old without any significant medical history, not taking medications, and with a normal maximal stress echocardiogram were eligible. Global and regional longitudinal strain (LS) was evaluated by 2D speckle tracking echocardiography. Results One hundred and seventy pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
3
1
0
Order By: Relevance
“…Interestingly, we found a base to apex gradient in LV regional LS abnormalities, with apical segments being less affected. This pattern has already been described in other cardiac diseases such as systemic hypertension [24], and recently reported by our group in a cohort of pediatric patients with previous asymptomatic or mildly symptomatic COVID-19 without MIS-C development [25]. Of interest, other studies on different populations have already demonstrated the prognostic value of GLS [26].…”
Section: Longitudinal Strainsupporting
confidence: 80%
“…Interestingly, we found a base to apex gradient in LV regional LS abnormalities, with apical segments being less affected. This pattern has already been described in other cardiac diseases such as systemic hypertension [24], and recently reported by our group in a cohort of pediatric patients with previous asymptomatic or mildly symptomatic COVID-19 without MIS-C development [25]. Of interest, other studies on different populations have already demonstrated the prognostic value of GLS [26].…”
Section: Longitudinal Strainsupporting
confidence: 80%
“…In our study, there is a positive association between the GLS and BMI. Impairment of the LV-EF and GLS by overweight and obesity is also known from other studies [47][48][49]. The parameters of diastolic function are within the normal range in our studied athletes but are significantly reduced in the PCAt.…”
Section: Discussionsupporting
confidence: 86%
“…There was a positive association between GLS and BMI in our study. Impairment of LV-EF and GLS by overweight and obesity is also known from other studies (39)(40)(41). Parameters of diastolic function were within the normal range in our studied athletes but were significantly reduced in PCAt.…”
Section: Initial Symptoms and Correlation Analysis With Gls And Grssupporting
confidence: 55%